Strategi Kepemimpinan Transformasional dalam Mengatasi Resistensi Guru terhadap Adopsi Teknologi Pembelajaran di Sekolah Swasta Kabupaten Brebes - Dwi Mei Diana Sintiyawati (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the transformational leadership strategies of principals in overcoming teacher resistance to the adoption of learning technology in private schools in Brebes Regency. The research method used a qualitative approach, with participants consisting of principals, teachers, and students in several private schools implementing learning technology. Data was collected through in-depth interviews, observation, and documentation, then analyzed thematically using source triangulation to increase the validity of the findings. The results indicate that principals implement transformational leadership through four main strategies: (1) idealized influence, by providing role models for technology use; (2) inspirational motivation, by building a collective vision and spirit; (3) intellectual stimulation, by encouraging teachers to think creatively and innovatively; and (4) individualized consideration, by providing personal attention and mentoring to teachers experiencing difficulties. These strategies have proven effective in reducing teacher resistance, increasing teacher readiness and motivation to adopt technology, and encouraging innovation in learning. The conclusions of this study indicate that principals' transformational leadership plays a crucial role in shaping a technology-adaptive school culture, empowering teachers, and increasing the effectiveness of digital-based learning in private schools.   Keywords: Transformational Leadership, Teacher Resistance, Adoption of Learning Technology, Private Schools, Brebes Regency